2016
DOI: 10.3899/jrheum.151105
|View full text |Cite
|
Sign up to set email alerts
|

Low Risk of Hepatitis B Virus Reactivation in HBsAg-negative/Anti-HBc–positive Carriers Receiving Rituximab for Rheumatoid Arthritis: A Retrospective Multicenter Italian Study

Abstract: The administration of RTX + DMARD in patients with RA with resolved HBV infection leads to a negligible risk of HBV reactivation, thus suggesting that serum HBsAg and/or HBV DNA monitoring but not universal anti-HBV prophylaxis is justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 30 publications
2
28
0
2
Order By: Relevance
“…The differences in findings between the few reports available may result from differences in follow-up time, sample size, monitoring policy, the definition of HBV reactivation and race. In an Italian multicenter study of patients receiving a median of 3 cycles of RTX (range, 1-8) over 34 months of follow-up (range, 0-80), the risk of HBV reactivation was 3% (1/33) in HBsAg − /HBcAb + patients 16 . A cohort study from Taiwan with a follow-up of 3.4 ± 1.7 years from RTX initiation reported an HBV reactivation rate of approximately 9.1% (4/44) 15 , consistent with that observed in our study (8%; 4/50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences in findings between the few reports available may result from differences in follow-up time, sample size, monitoring policy, the definition of HBV reactivation and race. In an Italian multicenter study of patients receiving a median of 3 cycles of RTX (range, 1-8) over 34 months of follow-up (range, 0-80), the risk of HBV reactivation was 3% (1/33) in HBsAg − /HBcAb + patients 16 . A cohort study from Taiwan with a follow-up of 3.4 ± 1.7 years from RTX initiation reported an HBV reactivation rate of approximately 9.1% (4/44) 15 , consistent with that observed in our study (8%; 4/50).…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort study conducted in a regional hospital in Taiwan, approximately 9.1% of HBsAg − /HBcAb + RA patients (4/44) experienced HBV reactivation approximately 2 years after receiving RTX 15 . In a retrospective multicenter Italian study, the HBV reactivation rate was low (3%; 1/33) in HBsAg − /HBcAb + patients 16 . Only one patient became positive for HBV DNA after 6 months of RTX treatment and was effectively treated with lamivudine, which prevented hepatitis flare-ups.…”
mentioning
confidence: 94%
“…Although a previous study demonstrated no rHBV in RTX‐treated rheumatic patients with resolved HBV infection, rHBV has recently been recognized as a complication characterized by a seroreversion of HBsAg in HBsAg‐negative patients receiving RTX therapy . Despite these findings, there are limited data or even conflicting results on rHBV in RTX‐treated patients . In addition, the risk factors of rHBV in HBsAg‐negative, HBcAb‐positive RA patients with prior HBV infection have yet to be defined.…”
Section: Introductionmentioning
confidence: 99%
“…A multi-center study concluded that combination of rituximab and DMARDs in patients with Rheumatoid arthritis (RA) had a negligible risk of HBVr. They therefore recommended serum monitoring but not prophylaxis in these patients 7 . Thus, the decision of using anti-viral prophylaxis to prevent reactivation of HBV infection remains controversial, although strong evidence exists in the favor of prophylaxis.…”
Section: Discussionmentioning
confidence: 99%